A Feminist Islamic Review of Abdul Basit's Thoughts on Optimising Women's Majelis Taklim - Khikmatun Rahmadhani; Dewi Ayu Narasati; Nadia Milatalia; Aulia Nur Indah; Lugas Legi Diana; Tegar Baehaqi; Sofiatun (International Tatho Academics, 2025)
Women's Majelis Taklim have not been fully utilised as a means of empowerment with transformative impact. Women's Majelis Taklim have not been fully utilised as a means of empowerment with transformative impact. This qualitative research, in the form of a literature review, aims to identify Abdul Basit's thoughts on the role of Majelis Taklim as a space for developing women's capacity in the social da'wah movement. Through an Islamic feminist approach as an analytical framework, this study concludes that, according to Abdul Basit's thoughts, the professional management of women's Majelis Taklim can be synergised with social empowerment programmes, so that women's Majelis Taklim can play an active role as agents of change. This research contributes to the existence of women's Majelis Taklim as a strategic space to strengthen women's participation and leadership roles in actively transforming Islamic teachings in social life.